2017
DOI: 10.3390/d9020022
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Gaps of Knowledge for Naming and Distinguishing Multiple Species of Crown-of-Thorns-Seastar in the Acanthaster planci Species Complex

Abstract: Nearly a decade ago, DNA barcoding (partial mitochondrial COI gene sequences) showed that there are at least four species in the Indo-Pacific within what was previously conceived to be a single Crown-of-Thorns-Seastar (COTS) species, Acanthaster planci. Two of these species-A. planci Linnaeus, 1758, distributed in the North Indian Ocean, and A. mauritiensis de Loriol, 1885, distributed in the South Indian Ocean-have been already unequivocally named. In contrast, the Pacific COTS (proposed name: A. solaris (Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 43 publications
3
54
0
1
Order By: Relevance
“…The relatively high (8.8-10.6%) genetic distance among the four-aforementioned species, based on the COI marker used for 'barcoding', suggests that these species diverged 1.95 to 3.65 million years ago (Vogler et al 2008). Within the four nominal species, genetic divergence was greatest for the Pacific population (Haszprunar et al 2017), and other studies have revealed conspicuous genetic structure when comparing among CoTS from different regions across the Pacific (Timmers et al 2012;Vogler et al 2013). Moreover, distinctive phenotypes of Acanthaster spp.…”
Section: Systematics and Biogeographymentioning
confidence: 99%
See 4 more Smart Citations
“…The relatively high (8.8-10.6%) genetic distance among the four-aforementioned species, based on the COI marker used for 'barcoding', suggests that these species diverged 1.95 to 3.65 million years ago (Vogler et al 2008). Within the four nominal species, genetic divergence was greatest for the Pacific population (Haszprunar et al 2017), and other studies have revealed conspicuous genetic structure when comparing among CoTS from different regions across the Pacific (Timmers et al 2012;Vogler et al 2013). Moreover, distinctive phenotypes of Acanthaster spp.…”
Section: Systematics and Biogeographymentioning
confidence: 99%
“…The third major species (A. mauritiensis) is generally restricted to the south-western Indian Ocean, but does co-occur with A. planci in the Oman Sea (Vogler et al 2008). There is also a fourth distinct species restricted to the Red Sea, which is yet to be formally described and named (Haszprunar et al 2017). The relatively high (8.8-10.6%) genetic distance among the four-aforementioned species, based on the COI marker used for 'barcoding', suggests that these species diverged 1.95 to 3.65 million years ago (Vogler et al 2008).…”
Section: Systematics and Biogeographymentioning
confidence: 99%
See 3 more Smart Citations